HJT-sRNA-m7 bencaosome modulates fibrosis progression in a silicosis mouse model - CHANG Jiahui, REN Pengju, ZHOU Yunyi, JIANG Chengyu, ZHANG Yanli (Jichu yixue yu linchuang)
Objective To explore the role and mechanism of HJT-sRNA-m7 (M7) bencaosome in a silicosis mouse model. Methods C57BL/6J mice were randomly divided into four groups: blank, control, negative control (NC) oligonucleotide, and M7 treatment (HJT-sRNA-m7 bencaosome) groups. After three rounds of pretreatment with HJT-sRNA-m7 bencaosome, all groups except the blank one were modeled via a single intratracheal exposure. Each mouse received 50 μL of a silica suspension at a dose of 200 mg/kg body weight via intratracheal instillation. From day 6 to day 26, the bencaosome was administered every other day via oral gavages. On day 28, pulmonary function tests were performed. Bronchoalveolar lavage fluid was collected for flow cytometry and cytokine analysis. The left lung was harvested for histopathological examination and Masson′s trichrome staining to evaluate collagen fiber deposition. The right lung was used for hydroxyproline quantification to assess collagen accumulation. Results The results of pulmonary function test, pathological analysis and hydroxyproline measurements all indicated that M7 bencaosome treatment significantly alleviated silica-induced pulmonary fibrosis. Moreover, flow cytometry analysis of BALF confirmed that M7 bencaosome inhibited the silica-induced inflammatory response, that was supported by cytokine analysis. Conclusions HJT-sRNA-m7 bencaosome is quite effective to treat silicosis and inhibits mitigating pulmonary fibrosis progression in mouse models.